Stimulated Glanzmann’s Thrombasthenia Platelets Produce Microvesicles - Holme, Pål André; Solum, Nils Olav; Brosstad, Frank; Egberg, Nils; Lindahl, Tomas L (Thrombosis and Haemostasis, 1995)
The mechanism of formation of platelet-derived microvesicles remains controversial.The aim of the present work was to study the formation of microvesicles in view of a possible involvement of the GPIIb-IIIa complex, and of exposure of negatively charged phospholipids as procoagulant material on the platelet surface. This was studied in blood from three Glanzmann’s thrombasthenia patients lacking GPIIb-IIIa and healthy blood donors. MAb FN52 against CD9 which activates the complement system and produces microvesicles due to a membrane permeabilization, ADP (9.37 μM), and the thrombin receptor agonist peptide SFLLRN (100 μM) that activates platelets via G-proteins were used as inducers. In a series of experiments platelets were also preincubated with PGE1 (20 μM). The number of liberated microvesicles, as per cent of the total number of particles (including platelets), was measured using flow cytometry with FITC conjugated antibodies against GPIIIa or GPIb. Activation of GPIIb-IIIa was detected as binding of PAC-1, and exposure of aminophospholipids as binding of annexin V. With normal donors, activation of the complement system induced a reversible PAC-1 binding during shape change. A massive binding of annexin V was seen during shape change as an irreversible process, as well as formation of large numbers of microvesicles (60.6 ±2.7%) which continued after reversal of the PAC-1 binding. Preincubation with PGE1 did not prevent binding of annexin V, nor formation of microvesicles (49.5 ± 2.7%), but abolished shape change and PAC-1 binding after complement activation. Thrombasthenic platelets behaved like normal platelets after activation of complement except for lack of PAC-1 binding (also with regard to the effect of PGE1 and microvesicle formation). Stimulation of normal platelets with 100 μM SFLLRN gave 16.3 ± 1.2% microvesicles, and strong PAC-1 and annexin V binding. After preincubation with PGE1 neither PAC-1 nor annexin V binding, nor any significant amount of microvesicles could be detected. SFLLRN activation of the thrombasthenic platelets produced a small but significant number of microvesicles (6.4 ± 0.8%). Incubation of thrombasthenic platelets with SFLLRN after preincubation with PGE1, gave results identical to those of normal platelets. ADP activation of normal platelets gave PAC-1 binding, but no significant annexin V labelling, nor production of microvesicles. Thus, different inducers of the shedding of microvesicles seem to act by different mechanisms. For all inducers there was a strong correlation between the exposure of procoagulant surface and formation of microvesicles, suggesting that the mechanism of microvesicle formation is linked to the exposure of aminophospholipids. The results also show that the GPIIb-IIIa complex is not required for formation of microvesicles after activation of the complement system, but seems to be of importance, but not absolutely required, after stimulation with SFLLRN.